Pengaruh Event Marketing Dan Influencer Marketing Terhadap Keputusan Pembelian Diamond Pada Games Online Mobile Legends (Studi Pada Konsumen Shop Mobile Legends di Universitas Islam Malang) - Indirwan, Mohamad Fadhil; Basalamah, Muhammad Ridwan; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract In this digital era, society's life is closely intertwined with rapidly evolving technology, particularly in the entertainment industry, one of which is the gaming sector. One of the highly popular online games in Indonesia is Mobile Legends, a Multiplayer Online Battle Arena game developed by Moonton. The significant interest of Indonesian society in Mobile Legends has created numerous business opportunities, including the virtual item top-up business such as diamonds. The aim of this study is to investigate whether Event Marketing and Influencer Marketing have an impact on diamond purchasing decisions in the online game Mobile Legends. This research adopts an Explanatory Research approach with a quantitative method. The population of this study comprises active students of the Islamic University of Malang. The sample size used is 88 respondents, determined using the Slovin formula. Hypothesis testing in this study employs the F-test and t-test with the SPSS version 22 software for data analysis. The test results reveal that both Event Marketing (X1) and Influencer Marketing (X2) have a simultaneous positive and significant influence on diamond purchasing decisions (Y). Keywords: Purchase Decision, Event Marketing, Influencer Marketing